Pengaruh Variasi Suhu Kalsinasi terhadap Struktur Kristal dan Sifat Mekanik Hidroksiapatit dari Limbah Cangkang Kerang Mutiara - Susi Rahayu; Dian W. Kurniawidi; Siti Rubi’ah; Hurnah Hurnah; Abdul Gani; Siti Alaa (Universitas Hamzanwadi, 2025)
Hydroxyapatite (HAp is widely known as a promising biomaterial because its chemical composition closely resembles that of human bone and teeth, making it suitable for biomedical uses such as bone tissue engineering and implant materials. This study explores how variations in calcination temperature (750–950 °C) affect the crystal structure and mechanical properties of HAp synthesized from Pinctada maxima shells—a calcium-rich biogenic waste. The crystal structure was analyzed using X-ray Diffraction (XRD), while mechanical properties were evaluated using a Tensilon testing machine. The XRD results showed a phase shift from the dominance of tricalcium phosphate (TCP) at low temperatures towards the dominant HAp phase at high calcination temperatures with improved crystallinity from 33.94% to 45.89%. The mechanical tests showed compressive strength values of 0.1981 to 0.3148 MPa and the elastic modulus of 14.941 to 26.721 MPa. The higher calcination temperature tends to increase the cristallinity, density, and compressive strength, but reduced elasticity due to a stiffer internal structure. These results indicate that changes in crystal structure have a direct effect on increasing the compressive strength and stiffnes of the material. This study confirms the potential ofPinctada maxima shells as a sustainable calcium source for producing high-quality hydroxyapatite suitable for biomedical applications.